NUNS, SIGNATURES, AND LITERACY IN LATE-CAROLINGIAN CATALONIA. (2019) - JARRETT, JONATHAN
Abstract : It is somewhat rare to be able to analyze the membership of an early medieval women's religious community in any detail. Sant Joan de Ripoll, which operated from the late ninth century until 1017 at modern-day Sant Joan de les Abadesses in Catalonia, provides not just this opportunity but the even rarer chance to evaluate the nuns' command of writing, by means of a single original charter of 949 that several of them signed autograph. This article argues that the signatures of these nuns indicate that they had in fact been taught to write before joining the nunnery. They are thus a source for female lay, rather than religious, literacy in this time and area. Consolidating this, the article provides a prosopography of the known nuns derived from the other charters of the nunnery's part-surviving archive, including tracing some of their careers beyond the 1017 dissolution of the house. This shows that the members of the comital family who had founded the house and provided several of its abbesses were not otherwise frequent among the nuns; rather, the nunnery recruited from the local notables in its neighborhoods, to whose interest in female literacy these signatures therefore testify. Such support could not prevent the closure of the house, however, and the article closes with a reflection on the agency available to the nuns in a political sphere dominated by male, secular interests.